PENGARUH LEVERAGE, PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS:: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Christella, Chintya; OSESOGA, MARIA STEFANI (Ultimaccounting Jurnal Ilmu Akuntansi, 2019)
The objective of this research is to obtain empirical evidence about the effect of leverage, profitability, institutional ownership, liquidity, and firm size toward financial distress. In this study, leverage was measured by Debt Ratio (DTA), profitability was measured with Net Profit Margin (NPM) and liquidity was measured by Current Ratio (CR). While financial distress was measured by Altman Z-score. Sample in this research was selected by using purposive sampling method and the secondary data used in this research is analyzed by using multiple regression method. The samples in this research were 23 firms that has been registered as manufacturer sector industry in the Bursa Efek Indonesia (BEI) for the year 2014-2016 consecutively. The results of this study are (1) leverage (DTA) has significant effect towards financial distress, (2) profitability (NPM) has significant effect on financial distress, (3) institutional ownership does not affect financial distress, (4) liquidity (CR) does not affect financial distress, and (5) firm size does not affect financial distress.